Timur ve Anadolu I: Timur'un Uluborlu ve Eğridir'i Zaptı - (:unkn) unknown (My University, 2004)
0

Timur continued his conquest of Anatolia during the summer of 1402 following the Ankara War. He stayed eight and a half months in Anatolia. First he conquered Izmir ( Smyrna ) on December 1402, then marched to Uluborlu and Eghridir. The reason why he conquered these last two wealthy cities was to occupy the Hamidoghullari Principality. Through this policy he tried to establish an economic blockade against the Ottoman State. This was for fear of retaliation by the Ottoman State. This article attempts to clarify the reasons and the results of this event in a wide perspective. The author uses as his main sources texts by early Ottoman historians, and also takes into consideration recent literature on the Topic.
Keywords: Tarih